Efficacy and safety of first-line sunitinib in Chinese patients with metastatic renal cell carcinoma. (2nd May 2018) - Qin, Shu-Kui; Jin, Jie; Guo, Jun; Wang, Jin-Wan; Zhou, Fang-Jian; Huang, Yi-Ran; Ren, Xiu-Bao; Ye, Ding-Wei; Pan, Sharon; Sajben, Peter; Wang, Qiao
Aim: We report the first prospective study of sunitinib for metastatic renal cell carcinoma (mRCC) in China.Methods: Chinese mRCC patients received first-line sunitinib 50 mg daily (4/2 regimen). Overall survival (OS), progression-free survival (PFS), objective response rate and safety were assessed. Potential efficacy biomarkers were explored in post hoc analyses.Results: Median PFS was 61.7 weeks; median OS was 133.4 weeks; objective response rate was 31.1%. Most frequent adverse events (AEs) were: hand–foot syndrome (63.8%), decreased white blood cell count (52.4%), fatigue (51.4%) and decreased platelet count (51.4%). AEs were identified that predicted longer PFS and OS.Conclusion: Sunitinib showed efficacy and manageable AE profile in treatment-naive Chinese mRCC patients. Larger prospective studies are required to confirm identified AEs as predictors of efficacy.